REPRODUCTIVE PERFORMANCE OF DOMESTICATED BROODSTOCK OF SILVER PERCH, Bidyanus bidyanus (MITCHELL 1838) AND THE RELATIONSHIP BETWEEN OIL GLOBULE FRAGMENTATION AND EGG QUALITY - Sulaeman Sulaeman; Ravi Fotedar (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2017)
The experiments investigated the reproductive performance of the domesticated broodstock of the silver perch and the relationship between various degrees of oil globule fragmentation and egg quality. Six years old of second generation broodstock (n=3) were evaluated based on the fecundity, fertilisation rate, hatching rate, the degree of oil fragmentation of egg, and the quality of embryos and larvae produced. The fragmentation were grouped into three categories: un-fragmented (cat-1), moderately fragmented (cat-2), and highly fragmented (cat-3). The results showed that the broodstock had a relatively high fecundity (132,400 ± 7,22), fertilization rate (94.27 ± 1.28%), and hatching rates (87.94 ± 1.23%). The survival rate of larvae at 12 days post hatching (dph) in cat-1 (71.3 ± 0.9%) was higher than cat-2 (66.7 ± 0.9%) whereas cat-2 was higher than cat-3 (61.3 ± 0.3%). The eggs was dominated by cat-1 (78.11 ± 2.44%) which was significantly higher than cat-2 (21.26 ± 2.45%) and cat-3 ones (0.40 ± 0.21%). The survival rate of embryo at 20 hours post spawning (hps) and hatching rate of cat-1 (95.33 ± 0.00% and 93.33 ± 0.00%) and cat-2 (90.00 ± 0.00% and 85.00 ± 0.00%) were significantly higher than cat-3 (72.33 ± 1.76% and 60.33 ± 0.00%). The total length (TL) of the larvae of cat-1 and cat-2 (8.44 ± 0.21 mm and 8.35 ± 0.23 mm respectively) were significantly higher than larvae of cat-3 (7.09 ± 0.14 mm). No significant difference was found in the larval deformities among any categories. In conclusion, the reproductive performance of six year-old broodstock silver perch showing acceptable performance and egg categorisation based on oil globule fragmentation can be used as a useful tool to indicate eggs quality of silver perch.